A study on stress as mediating variabale in the relationship between personality and job satisfaction among hotel employees in Malaysia / Farah Liyana Bustamam - Bustamam, Farah Liyana (2010)
The hospitality industry is one of the most aggressive industries in terms of competition amongst rivals to win the market share. As to remain competitive, hotels are keen to probe into factors which may result to the ups or downs of an organization. Being part of the ‘people oriented’ industry, hotel organizations are to abide by the fact that their performances are measured through customers’ satisfaction. Due to this, human capital has been identified to be one of the key factors in determining the success or failure of a business. Hence, it is crucial for hotel organizations to select the right people with the right personality to represent the organizations. However, individuals in the organization could be as subjective and could not deny the inevitable presence of stress which would cause behavioral change, and in turn may affect their job satisfaction. A total of 36 4-star and 5-star hotels in Kuala Lumpur were chosen and 165 employees participated in this study. Data were collected through self-administered survey questionnaires. Descriptive statistics, reliability analysis and multiple regressions analyses were used in the data analysis. According to the empirical analytic results, extroversion was found to have the highest standardized beta coefficient (β = 0.40, p<.01) and determined as the most significant influence on job satisfaction. On the other hand, the beta value for neuroticism (β = 0.15, p<.05) was low which indicated that it made less contribution on job satisfaction. However, the regressions analyses of this study revealed that stress mediated the relationship between personality and job satisfaction in which two out of five personality traits used in this study were found to be partially mediated by stress; Openness (β=.32, p<0.01) and extroversion (β=.23, p<0.05). Therefore, it could be concluded that not all personality traits could be affected by stress. Based on the results above, Hypothesis 1 (H1b) and Hypothesis 3 (H3) particularly were accepted and supported by the findings. From the study, one can have a greater understanding of to what extent personality types contribute to job stress and how job satisfaction could also be affected. In addition, this study provides a basis especially for the hospitality industry researcher to further test the relationships among these constructs.